Global, Regional and Local Influences in The Relationship between Asset Returns and The Macro Economic Factors in India - Arora, Akshay (2009)
Asset pricing is a well researched topic in financial studies. This topic holds interest as it is directly related with the concept of wealth creation. Asset prices move with changes in the environment (Cheung and Ng, 1998). The changes including business environment, economic policies, social factors and political movements affect the asset pricing and in turn the expected returns from these assets. The asset pricing models developed so far have been reasonably successful in determining the relationship between extrinsic factors and the value of assets (Levine and Zervos, 1998). The models also highlight the degree of effects of such external movements to the asset pricing.